Processed multinet CTD data from METEOR cruise M123 - Michael Siccha; Michal Kucera (PANGAEA, 2018)
Research expedition M123 took place from February 3rd (Walvis Bay, Namibia) to February 27th (Cape Town, South Africa), 2016. CTD data for 3 stations along the cruise track were recorded using a Sea & Sun Technology CTD90M (SN 979) down to depths of 700m. The CTD was equipped with the following sensors: Temperature sensor Pt100 model 1509 (Thermal Developments International), Conductivity sensor 7-pole platinum coated electrode cell in quartz glass (Sea & Sun Technology), Seapoint Chlorophyll Fluorometer (Seapoint) and single rod electrode ph sensor (AMT Analysenmesstechnik GmbH). The data files contain the data for temperature, salinity, density, chlorophyll a concentration and pH; as raw data and processed and flagged according to the recommendations for real-time data processing of EuroGOOS and GTSPP, as well as the outlier detection method CoTeDe (https://github.com/castelao/CoTeDe). Biogeographic regions are determined according to Spalding et al. (2012). TEOS-10 unit conversions have been performed with the GSW Oceanographic Toolbox (McDougall and Barker, 2011).